The Influence of E-WOM Through Social Media TikTok on Aerostreet Product Brand Awareness - Angga Kadarusman; Yuliani Rachma Putri (PT Mattawang Mediatama Solution, 2024)
The development of technology has had a huge impact on business actors in marketing their products. The dissemination of information about marketed products can develop rapidly in a more effective and efficient manner. From this phenomenon, business people take advantage of promotions through EWOM or word of mouth promotions on social media. Social media that is currently popular with various groups in Indonesia is Tiktok. This research aims to determine whether or not there is an influence of Electronic Word of Mouth on brand awareness of Aerostreet products on Tiktok which can influence consumer purchasing decisions. This research uses an associative method to see the influence of one variable on other variables using a quantitative approach. The research results show that the hypothesis test shows that the T value is greater than the T table, namely T count is 15,323 and T table is 1,922. This means that Electronic Word of Mouth has a significant influence on brand awareness of the Aerostreet brand on Tiktok.